Variation in Leaf Respiration Rates at Night Correlates with Carbohydrate and Amino Acid Supply - O’Leary, Brendan M. (Plant Physiol, 2017)
Plant respiration can theoretically be fueled by and dependent upon an array of central metabolism components; however, which ones are responsible for the quantitative variation found in respiratory rates is unknown. Here, large-scale screens revealed 2-fold variation in nighttime leaf respiration rate (R(N)) among mature leaves from an Arabidopsis (Arabidopsis thaliana) natural accession collection grown under common favorable conditions. R(N) variation was mostly maintained in the absence of genetic variation, which emphasized the low heritability of R(N) and its plasticity toward relatively small environmental differences within the sampling regime. To pursue metabolic explanations for leaf R(N) variation, parallel metabolite level profiling and assays of total protein and starch were performed. Within an accession, R(N) correlated strongly with stored carbon substrates, including starch and dicarboxylic acids, as well as sucrose, major amino acids, shikimate, and salicylic acid. Among different accessions, metabolite-R(N) correlations were maintained with protein, sucrose, and major amino acids but not stored carbon substrates. A complementary screen of the effect of exogenous metabolites and effectors on leaf R(N) revealed that (1) R(N) is stimulated by the uncoupler FCCP and high levels of substrates, demonstrating that both adenylate turnover and substrate supply can limit leaf R(N), and (2) inorganic nitrogen did not stimulate R(N), consistent with limited nighttime nitrogen assimilation. Simultaneous measurements of R(N) and protein synthesis revealed that these processes were largely uncorrelated in mature leaves. These results indicate that differences in preceding daytime metabolic activities are the major source of variation in mature leaf R(N) under favorable controlled conditions.